Diseño de una red hidráulica, automatizada, para la optimización del lavado de filtros de la planta de tratamiento de agua potable de Guasca, Cundinamarca (2017)
The current conditions of operation of the aqueduct of the population of Guasca, Cundinamarca, were evaluated. The conceptual design was developed and parameters were defined for the hydraulic network. Alternatives of the filtered bed subsystem composed of sand and anthracite sand bed were proposed and evaluated. When choosing an alternative of the solution that was conceptualized, the development of the detailed design of the red hydraulics was proposed, the next step was the elaboration of the panels. In order to make the user more clear of the characteristics of the red, the manual of operation, assembly and maintenance was elaborated, a simulation of the automation of the filtration process was carried out. Finally, the respective financial analysis of the total cost to develop the hydraulic network was carried out.